2018
DOI: 10.1002/admt.201800104
|View full text |Cite
|
Sign up to set email alerts
|

Visible and Near‐Infrared Imaging with Nonfullerene‐Based Photodetectors

Abstract: The solution‐processed organic photodetectors underpin an emerging technology with inherent implications in the biological sensors and imaging displays. Conventional organic photodiodes, the core element of an organic photodetector, rely mainly on fullerene‐based acceptors, which in combination with high and middle bandgap donors, limit the spectral photosensitivity to the visible range. Even in the case of low bandgap polymers the oscillator strength and thus the extinction coefficient are usually limited in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
124
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(130 citation statements)
references
References 39 publications
6
124
0
Order By: Relevance
“…24 The broad absorption of the P3HT:O-IDTBR system also made it attractive as a photodetector active layer, being sensitive to light from the visible to the near infrared regions. 25 Additionally, Baran et al showed that introducing a third component, namely O-IDFBR, into the P3HT:O-IDTBR blend increased the PCE up to 7.7%. 26 Interestingly, O-IDTBR also demonstrated great performance when blended with other wide band-gap polymers (PvBDTTAZ and PBDTTT-EFT), exceeding 11% PCE.…”
Section: Introductionmentioning
confidence: 99%
“…24 The broad absorption of the P3HT:O-IDTBR system also made it attractive as a photodetector active layer, being sensitive to light from the visible to the near infrared regions. 25 Additionally, Baran et al showed that introducing a third component, namely O-IDFBR, into the P3HT:O-IDTBR blend increased the PCE up to 7.7%. 26 Interestingly, O-IDTBR also demonstrated great performance when blended with other wide band-gap polymers (PvBDTTAZ and PBDTTT-EFT), exceeding 11% PCE.…”
Section: Introductionmentioning
confidence: 99%
“…Reported D * values were calculated using Equation , unless otherwise stated. Interestingly, fullerene derivatives are used as electron acceptors in all work, except for some recent exceptions . This implies that the difference in optical and electrical characteristics reported here are largely due to the different polymers used as donor materials.…”
Section: Dark Current In Opds: Origin and Solutionsmentioning
confidence: 98%
“…For instance, Li et al reported a record power conversion efficiency of 14.62% from a single organic junction, and Meng et al boosted the efficiency further to 17.3% through a 2‐terminal tandem architecture . Organic photodetectors (OPDs) based on the BHJs have also shown remarkable device performance, competing with the commercial silicon photodiodes as an alternative technology for next generation photodetection and imaging . Moreover, OPDs can even outperform silicon photodiodes on some metrics, benefiting from the chemical versatility, tunable absorption spectra, and low‐energy embedded solution‐processing …”
Section: Introductionmentioning
confidence: 99%